Graphitic-C3N4 quantum dots modified carbon nanotubes as a novel support material for a low Pt loading fuel cell catalyst. Issue 38 (31st March 2016) - Li, Cun-Zhi; Wang, Zhen-Bo; Sui, Xu-Lei; Zhang, Li-Mei; Gu, Da-Ming
Abstract : A novel graphitic-C3 N4 quantum dot modified carbon nanotube composite supported PtRu catalyst is prepared by π–π stacking. The enhanced catalytic performance of the catalyst is due to the better dispersion of PtRu NPs and the strong metal–support interaction (SMSI). Abstract : For developing low Pt loading and high performance catalysts for direct methanol fuel cells, a graphitic-C3 N4 quantum dots (g-C3 N4 QDs) modified CNT (CNT-QDs) composite material was constructed via a π–π stacking method, in which the g-C3 N4 QDs act a bridged unit between the CNTs and metal nanoparticles (NPs). Compared to conventional acid-functionalized CNTs used for supporting novel metal NPs, the CNT-QDs have less structural damage leading to their high stability. Moreover, the electrochemical test results indicate that the mass catalytic activity of the PtRu/CNT-QDs catalyst is 2.3 times higher than that of PtRu/CNT, leading to a 56.5% reduction of novel metal loading. The accelerated potential cycling tests (APCTs vs. RHE 0–1.2 V) show that the PtRu/CNT-QDs catalyst possesses 15.1% higher stability than that of the conventional acid-functionalized CNTs supported PtRu (PtRu/T-CNT) catalyst. The significantly enhanced performance obtained for the PtRu/CNT-QDs catalyst was ascribed to the homogeneous dispersion of PtRu NPs on the composite support due to its abundant Lewis acid sites for anchoring the PtRu NPs and the excellent mechanical resistance and stability of the g-C3 N4 /CNT composite materials in acidic and oxidative environments, as well as the strong metal–support interaction (SMSI) between the metal NPs and g-C3 N4 .